Ticagrelor With or Without Aspirin After Complex PCI - Dangas, George; Baber, Usman; Sharma, Samin; Giustino, Gennaro; Mehta, Shamir; Cohen, David J; Angiolillo, Dominick J; Sartori, Samantha; Chandiramani, Rishi; Briguori, Carlo; Dudek, Dariusz; Escaned, Javier; et al. (Journal of the American College of Cardiology, 2020)
Whether a regimen of ticagrelor monotherapy attenuates bleeding complications without increasing ischemic risk in patients undergoing complex percutaneous coronary intervention (PCI) is unknown. The purpose of this study was to evaluate the effect of ticagrelor monotherapy versus ticagrelor plus aspirin in patients undergoing complex PCI from the randomized, double-blind, placebo-controlled TWILIGHT (Ticagrelor with Aspirin or Alone in High-Risk Patients after Coronary Intervention) trial. In the TWILIGHT trial, after 3 months of ticagrelor plus aspirin, event-free and adherent patients remained on ticagrelor and were randomly assigned to receive aspirin or placebo for 1 year. Complex PCI was defined as any of the following: 3 vessels treated, ≥3 lesions treated, total stent length >60 mm, bifurcation with 2 stents implanted, atherectomy device use, left main PCI, surgical bypass graft or chronic total occlusion as target lesions. Bleeding and ischemic endpoints were evaluated at 1 year after randomization. Among 7,119 patients randomized in the main trial, complex PCI was performed in 2,342 patients. Compared to ticagrelor plus aspirin, ticagrelor plus placebo resulted in significantly lower rates of Bleeding Academic Research Consortium (BARC) type 2, 3, or 5 bleeding (4.2% vs. 7.7%; hazard ratio [HR]: 0.54; 95% confidence interval [CI]: 0.38 to 0.76). BARC type 3 or 5 bleeding was also significantly reduced (1.1% vs. 2.6%; HR: 0.41; 95% CI: 0.21 to 0.80). There were no significant between-group differences in death, myocardial infarction, or stroke (3.8% vs. 4.9%; HR: 0.77; 95% CI: 0.52 to 1.15), nor in stent thrombosis. Among patients undergoing complex PCI who initially completed 3 months of ticagrelor plus aspirin, continuation of ticagrelor monotherapy was associated with lower incidence of bleeding without increasing the risk of ischemic events compared to continuing ticagrelor plus aspirin. (Ticagrelor With Aspirin or Alone in High-Risk Patients After Coronary Intervention [TWILIGHT]; NCT02270242).